“Dormancy” and “Awakening” Method Used for Fresh Mortar Waste Recycling and Reuse - Jin Pan; Liang Wang; Pengju Wang; Hao Wang; Ke Cao; Wenfeng Shen (Advances in Civil Engineering)
A safe and zero hazardous method is proposed to recycle and reuse fresh mortar waste. In this method, a dormancy agent and an awakening agent were used together in this study to reuse waste cement mortars. Citric acid (CA) was used as the dormancy agent to retard the hydration of cement, and an alkaline accelerator (AA) was used as the awakening agent to accelerate the hydration of cement retarded by CA at an early age. Autogenous shrinkage, dry shrinkage and quality loss, compressive strength, capillary water absorption, and rapid chloride penetration testing were performed for the mortars. A setting time test, X-ray diffraction, and thermogravimetric analysis (TGA) were performed for the pastes (without sand). The results showed that the addition of 0.3% of CA solution increased the setting time significantly. This was because the citrate ions were absorbed onto the surface of the cement particles and a protective film was formed around the cement particles to retard dissolution. However, the retarding effect was eliminated by the AA, which was mainly composed of sodium silicate due to the contribution to initial calcium consumption. With the increasing dosage of the AA, the autogenous shrinkage, dry shrinkage, water absorption, and total charges passed were increased continuously compared to the reference. However, the influence was insignificant at a low dosage of the AA (1% and 1.5%). Obviously, the compressive strengths of the mortars with the AA were increased compared with the reference at the curing times of 3 d and 7 d. On the basis of not reducing the compressive strength of mortar, the reutilization of fresh mortar waste is realized. From this work, it was found that the reuse of waste cement mortars was feasible with the combined utilization of CA and the AA, which could provide some theoretical basis and experimental data for engineering applications.